2012
DOI: 10.1002/ejlt.201100247
|View full text |Cite
|
Sign up to set email alerts
|

A novel conversion of sesamolin to sesaminol by acidic cation exchange resin

Abstract: Sesame (Sesamum indicum L.) seed and its oil contain abundant lignans, including sesamin, sesamolin, sesamol, sesaminol, and their glycosides. In the present study, a novel reaction pathway, using an anhydrous solvent system, cation exchange resin catalyst, and HPLC for detection, was employed for the conversion of sesamolin into sesaminol. Under optimal conditions of 5 mL toluene, 908C, initial sesamolin concentration of 6 mM, and catalyst dosage of 16.66 g/mmol of sesamolin, a 75.0% yield of sesaminol was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…We also observed that sesaminol accumulated during the first 40 min of incubation whereas the content of sesamol stayed relatively constant during the 100 min of hydrochloric acid treatment. Therefore, we agree with Huang et al [16] and consider the mechanism of the Villavecchia test for detecting sesame oil as follows. In brief, the unreliable sesamolin is firstly decomposed by concentrated hydrochloric acid into the primary products, sesamol and an intermediate oxonium ion, and afterward, the primary products undergo an electrophilic addition reaction of rearrangement for each other to generate sesaminol, and/or a portion of sesamol reacts with furfural to produce the chromogenic complex (Fig.…”
Section: Chromogenic Effect Of Sesame Oils Prepared By Different Roassupporting
confidence: 91%
See 2 more Smart Citations
“…We also observed that sesaminol accumulated during the first 40 min of incubation whereas the content of sesamol stayed relatively constant during the 100 min of hydrochloric acid treatment. Therefore, we agree with Huang et al [16] and consider the mechanism of the Villavecchia test for detecting sesame oil as follows. In brief, the unreliable sesamolin is firstly decomposed by concentrated hydrochloric acid into the primary products, sesamol and an intermediate oxonium ion, and afterward, the primary products undergo an electrophilic addition reaction of rearrangement for each other to generate sesaminol, and/or a portion of sesamol reacts with furfural to produce the chromogenic complex (Fig.…”
Section: Chromogenic Effect Of Sesame Oils Prepared By Different Roassupporting
confidence: 91%
“…Although both sesamolin and sesamol were contributive to the chromogenic reaction, sesamol was considered the real reactant of the Villavecchia reaction which was able to react with furfural to produce color complex. According to the results of Huang et al [16] and this study, we speculated that sesamolin was very unreliable with hydrochloric acid and would be decomposed into sesamol and an intermediate oxonium ion during the Villavecchia test, and subsequently the reactant sesamol could react with furfural to form the chromogenic complex and/or rearrange with the oxonium ion at the ortho position through the electrophilic addition to generate sesaminol. In our study, sesaminol could not be quantified directly due to the lack of a commercial standard.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The mechanism of these transformations has not been conclusively established. Based on their study on the conversion of sesamolin to sesaminol under anhydrous conditions catalyzed by sulfonic acid and on Fukuda’s original work [ 131 ], Huang and coworkers [ 132 ] suggested a two-step mechanism. According to their hypothesis, protonated sesamolin brakes down into sesamol and oxonium ion, both of which subsequently recombine into the products.…”
Section: Chemistry Of Sesame Lignansmentioning
confidence: 99%
“…It is important to note that STG displays only a negligible level of antioxidant activity in vitro [8], [9]. Moreover, the formation of bioactive sesaminol in sesame oils does not arise from the hydrolysis of STG; it is produced from sesamolin through acid catalysis during the bleaching step of the refining process of sesame oil production [10], [11]. STG occurs abundantly in sesame oil cake, and is produced as a by-product of sesame oil production in a large amount and can serve as an inexpensive source for the industrial production of sesaminol.…”
Section: Introductionmentioning
confidence: 99%